Experimentally approaching to reciprocal cloaks via annulus-dielectric-metamaterials. (10th July 2019) - Huang, Tsung-Yu; Lin, Jian-Hui; Lee, Tung; Yen, Ta-Jen
Abstract: Transformation optics has brought a wave of fanaticism among researchers to realize the first-ever invisible cloak over the past decade. Several relevant devices, including internal cloaks, external cloaks, and mantle cloaks, have already been proposed, with a few being experimentally demonstrated. Still, the proposed cloaks possess their insufficiencies to realize a reciprocal cloak. To better illustrate the cloak, here we report a new approach to a transformation-optics-based reciprocal cloak with designed dielectric-annulus-based metamaterials. Our results indicate we can easily control the anisotropic constitutive parameters at will. In addition, the as-fabricated cloak enables concurrent vision and movements of a hidden object, evidenced by both simulated and measured field distributions. More importantly, the cloak demands no bespoke design and is applicable to arbitrary electric-large objects. We affirm that we provide a method to developing the first-ever reciprocal cloak in experiments, and believe that the cloak could be further operated at visible ranges through the methodology we introduced, paving a route toward future applications in the fields of optics, physics, materials science, etc.